Pengaruh Profitabilitas, Leverage, Likuiditas, Ukuran, Dividen Dan Struktur Aset Terhadap Nilai Perusahaan Industri Farmasi - Endartono, Muhammad Fildza; Hady, Hamdy; Nalurita , Febria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to specify the factors that influence firm value. This study uses a sample of manufacturing companies in the pharmaceutical sub-sector listed on the Indonesian Stock Exchange (IDX) for the 2015-2020 period. The independent variables in this study include profitability, leverage, liquidity, firm size, dividend policy and asset structure. The dependent variable of this research is firm value. There are a total sample of 8 manufacturing companies in the pharmaceutical sub-sector obtained using purposive sampling technique. The conclusion of this panel data regression study is that leverage, liquidity, dividend policy and asset structure have a significant negative effect on firm value, while profitability and firm size have no effect on firm value. Companies are advised to pay attention to leverage, liquidity, dividend policy and asset structure because they have a negative effect on firm value. The results of this study are expected to provide information to companies and potential investors to pay attention to leverage, dividend policy liquidity and asset structure because they affect firm value.